Enhancing climate resilience of monetary policy implementation in the euro area - Jana Aubrechtová; Elke Heinle; Rafel Moyà Porcel; Boris Osorno Torres; Anamaria-Valeria Piloiu-Popescu; Ricardo Queiroz; Torsti Silvonen; Lia Vaz Cruz (European Central Bank (ECB), 2023)
Central banks around the world are increasingly monitoring climate change risks and how these affect their balance sheets and their monetary policy transmission. The European Central Bank (ECB) extensively reviewed its monetary policy implementation framework in 2020-21 to better account also for climate change risks. This paper describes these considerations in detail to provide a holistic perspective of one central bank's climate-related work in relation to its monetary policy implementation framework. The paper starts by characterising the strategic reflections behind the principles of the enhanced framework and their relationship with the ECB monetary policy strategy review. Climate-related disclosures, improvements in risk assessment, a strengthened collateral framework and tilting of corporate bond purchases are the main pillars of the framework enhancements. The paper sheds light on the key motivations behind these enhancements, including the aspects that were reviewed but left unchanged. It also takes stock of the different challenges involved in the identification and estimation of climate change-related risk, how these can be partially overcome, and when they cannot be overcome, how they can constrain the ability of financial institutions, including central banks, to take further action. The integration of climate change considerations into the monetary policy implementation framework is at its inception. As data availability and quality improve, and risk methodologies develop, central banks will be able to deepen their approach. This paper also examines possible future avenues that central banks, including the ECB, might take to further refine their monetary policy implementation using an assessment framework for climate change-related adjustments.
Keywords: E52; E58; Q54; D53; 330; monetary policy implementation; climate change